The Antecedents and Consequences of Service Recovery Performance of Frontline Employees: A Study of Vietnam Retailing Industry - Van Hung , Tran; Lien, Vo Thi Ngoc (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
Previous studies on service recovery performance have merely focused on identifying the factors which affect it from the service provider side. This study investigates the effect of customer participation on Vietnam retailing service recovery performance. A structural model was developed and tested using data surveyed from 231 respondents who were currently full-time employees in Vietnam retailers. The results show that the more customer participation which frontline employees perceive, the more effective the service recovery they perform. Moreover, the results indicate that the more effective service recovery which frontline employees perform, the less stress they confront. Empowerment of and training for employees have an equivalent impact on the service recovery performance of frontline employees. However, there is no significant relationship between service recovery performance and intention to leave frontline employees.